2007
DOI: 10.1038/labinvest.3700539
|View full text |Cite
|
Sign up to set email alerts
|

FR-167653, a selective p38 MAPK inhibitor, exerts salutary effect on liver cirrhosis through downregulation of Runx2

Abstract: Liver cirrhosis remains a difficult-to-treat disease with a substantial morbidity and mortality rate. There is an emerging body of data purporting a pivotal role of the activated p38 mitogen-activated protein kinase (MAPK) in the process of cirrhosis. Several anticirrhotic agents have been developed over the past few years, and most of them exert their effects by indirectly inhibiting the p38 pathway. Effect of a selective p38 inhibitor is yet to be reported. In this study, we evaluated the salutary effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…There is no clear explanation for this occurrence, but in a previous study, it was observed that RUNX-2 expression was elevated in the livers of cirrhotic mice previously treated with CCl 4 29. The study called attention to RUNX-2 regulating collagen synthesis, demonstrating that myofibroblasts, including hepatic stellate cells and portal fibroblasts, express RUNX-2 29. This insightful study indicated that CCl 4 could up-regulate RUNX-2 in mesenchymal cells, unlike in osteoblasts 29.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is no clear explanation for this occurrence, but in a previous study, it was observed that RUNX-2 expression was elevated in the livers of cirrhotic mice previously treated with CCl 4 29. The study called attention to RUNX-2 regulating collagen synthesis, demonstrating that myofibroblasts, including hepatic stellate cells and portal fibroblasts, express RUNX-2 29. This insightful study indicated that CCl 4 could up-regulate RUNX-2 in mesenchymal cells, unlike in osteoblasts 29.…”
Section: Discussionmentioning
confidence: 95%
“…However, after disodium pamidronate treatment, the significant increase in the expression of RUNX2 in bone was restricted to animals treated with CCl 4 . There is no clear explanation for this occurrence, but in a previous study, it was observed that RUNX-2 expression was elevated in the livers of cirrhotic mice previously treated with CCl 4 29. The study called attention to RUNX-2 regulating collagen synthesis, demonstrating that myofibroblasts, including hepatic stellate cells and portal fibroblasts, express RUNX-2 29.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK was found independently increase ␣ 1 (I) collagen expression at transcriptional level. Additionally, both MAPK kinase (MKK) 3 and MKK6, two upstream kinases involved in activating p38 MAPK, have been shown to activate p38 MAPK in HSCs, which was associated with enhanced collagen expression in HSCs p38 MAPK is also found to increase the stability of ␣ 1 (I) collagen mRNA in untreated and activated HSCs (Cao et al, 2006;Hattori et al, 2007;Parsons et al, 2007). The secretion of type I collagen in acetaldehyde-induced HSCs are markedly inhibited by PD98059, a specific MEK inhibitor.…”
Section: Discussionmentioning
confidence: 95%
“…5 For this reason, liver cirrhosis is a disease that is difficult to treat and has a substantial morbidity and mortality rate. 6 In fact, treatment options for liver cirrhosis are very limited. 2 To date, there is no treatment available to reverse liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%